Corporate vs Community Head to Head: The Complexity of Land Tenure Conflict in Indonesia - Hariri, Achmad; Prakasa, Satria Unggul Wicaksana; Arifin, Samsul; Efendi, Ahmad Bahrul; Asis, Asis (Universitas Negeri Semarang, 2022)
At the end of 2018, residents replanted the land with thousands of banana trunks. In January 2019, Pakel residents were reported by P.T. Bumi Sari; the police summoned 11 residents. In 2020, residents established a command post and planted it for six months. However, in 2020 PT BUMI SARI said it had pocketed the latest Right to Cultivate, which entered some of the villages included in their Right to Cultivate (HGU.). However, a copy document is not owned by the head of the town and residents in Pakel village. This research is a field research or empirical legal research. This research is intended to analyze about the reclaiming reclaiming carried out by the Pakel community, whether it is justified. Futhermore, this research also analyze whether PT Bumi Sari's control of land in Pakel village is against the law. This research concluded that reclaiming by Pakel residents is the right of Pakel residents as with the purpose of the formation of the Basic Agrarian Law (UUPA), which is to bring prosperity, happiness, and justice to the State and the people, especially to the peasants. Right to Cultivate of PT Bumi Sari does not comply with the laws and regulations stipulated in the UUPA. and Government Regulation of the Republic of Indonesia Number 40 of 1996 concerning Cultivation Rights, Building Use Rights, and Land Rights.